2014
DOI: 10.1016/j.neurobiolaging.2013.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The role of ERK1, 2, and 5 in dopamine neuron survival during aging

Abstract: The extracellular signal-regulated kinases (ERKs) 1, 2, and 5 have been shown to play distinct roles in proliferation, differentiation, and neuronal viability. In this study, we examined ERK1, 2, and 5 expression and activation in the substantia nigra (SN), striatum (STR), and ventral tegmental area (VTA) during aging. An age-related decrease in phosphorylated ERK5 was observed in the SN and STR, whereas an increase in total ERK1 was observed in all three regions. In primary cultures of the SN and VTA, inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In a study by Ries et al (2009), the postnatal development of DA neurons of the substantia nigra in vivo was shown to be regulated, at least in part, by the signaling protein Akt/protein kinase B. Similarly, the extracellular signal‐regulated kinase (ERK) pathways have been demonstrated to be important for dopaminergic neuronal development, survival, and function (Cavanaugh et al, 2006a,b; Kim et al, 2006; Yoon et al, 2011; Parmar et al, 2014). For example, using primary dopaminergic mesencephalic cultures, we have shown that pharmacological inhibition of ERK5, and to a lesser extent ERK1 and 2, resulted in a significant loss of viability of dopaminergic neurons at day in vitro (DIV) 2, 4, 6, and 8 (Parmar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Ries et al (2009), the postnatal development of DA neurons of the substantia nigra in vivo was shown to be regulated, at least in part, by the signaling protein Akt/protein kinase B. Similarly, the extracellular signal‐regulated kinase (ERK) pathways have been demonstrated to be important for dopaminergic neuronal development, survival, and function (Cavanaugh et al, 2006a,b; Kim et al, 2006; Yoon et al, 2011; Parmar et al, 2014). For example, using primary dopaminergic mesencephalic cultures, we have shown that pharmacological inhibition of ERK5, and to a lesser extent ERK1 and 2, resulted in a significant loss of viability of dopaminergic neurons at day in vitro (DIV) 2, 4, 6, and 8 (Parmar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the extracellular signal‐regulated kinase (ERK) pathways have been demonstrated to be important for dopaminergic neuronal development, survival, and function (Cavanaugh et al, 2006a,b; Kim et al, 2006; Yoon et al, 2011; Parmar et al, 2014). For example, using primary dopaminergic mesencephalic cultures, we have shown that pharmacological inhibition of ERK5, and to a lesser extent ERK1 and 2, resulted in a significant loss of viability of dopaminergic neurons at day in vitro (DIV) 2, 4, 6, and 8 (Parmar et al, 2014). Moreover, others have shown that the regulation of dopaminergic neuronal development is regulated by D2 receptor‐mediated ERK activation (Kim et al, 2006; Yoon et al, 2011; Yoon and Baik, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The cell culture technique widely used for deriving neuronal cultures is the conventional monolayer [Yasuhara et al, 2006;Fasano et al, 2008;Mosharov et al, 2009;Babu et al, 2011;Walker et al, 2013;Walker and Kempermann, 2014]. The major limitation of this technique is that the neuron-glia ratio does not replicate the in vivo brain region, along with the low yields of specialized neuronal cells such as dopaminergic neurons [McNaught and Jenner, 1999;Fasano et al, 2008;Tolosa et al, 2013;Parmar et al, 2014;Brzozowski et al, 2015;Weinert et al, 2015]. This is probably because in a 2D format in vivo cell-cell interactions are limited, affecting the yield of neuronal and glial cells [Pardo and Honegger, 2000;Cukierman et al, 2002;Pampaloni et al, 2007;Justice et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that 2D monolayer primary midbrain culture results in either a very low yield (2-5%) of dopaminergic neurons or a reduced survival of these neurons in culture [Hyman et al, 1991;Fawcett et al, 1995;Fasano et al, 2008;Tolosa et al, 2013;Gaven et al, 2014;Parmar et al, 2014;Brzozowski et al, 2015;Weinert et al, 2015]. Certain other protocols have shown a yield as high as 40-90% of TH neurons in culture [Collier et al, 1990;Shimoda et al, 1992;Studer et al, 2000]; however, these yields do not reflect the in vivo situation.…”
Section: Introductionmentioning
confidence: 99%
“…In the nervous system, MAP2K/MAPK pathways are associated with neuronal cell death (Subramaniam et al 2004;Subramaniam and Unsicker 2010) and survival (Wang et al 2005;Cavanaugh et al 2006;Parmar et al 2014), as well as with neuropathic pain (Ma and Quirion 2005). In particular, MAPK7 has been implicated in neuronal survival and death (Cavanaugh 2004;Subramaniam et al 2004).…”
mentioning
confidence: 99%